Being a Man: Rethinking Vulgar Masculinity in Boyz N the Hood - Aryal, Bhushan (Literary Studies, 2016)
In this paper, I analyze the two versions—vulgar and bourgeois—of masculinity offered in the movie Boyz N the Hood, and argue that the movie’s advocacy of bourgeois masculinity as a solution to the woes facing inner city black communities in the United States is insufficient. Highlighting how masculinity is not an isolated position independent of identity politics such as feminism, I argue that the new conception of masculinity needs a progressive approach that can accommodate feminist and other related interests. While the paper is about the movie, the significance of the argument transcends a particular context: envisioning a progressive form of masculinity is as much the concern of black communities in the U.S. as it is of Nepali communities across the globe.